National Geographic Magazine [computer file] The 1970s (vol. 155, no. 4, April 1979) Jan. 1970-April 1973, May 1973-August 1976, September 1976-December 1979 (Washington, CD National Geographic Society, 1888)
Speak with Koko, an amazing gorilla that learned sign language. Travel to Ethiopia and unearth the remains of Lucy, one of humankind's oldest known ancestors. Join Thor Heyerdahl on a death-defying transatlantic sea voyage in a papyrus reed boat, the RA II. Study pollution, the scourge of the industrialized world, and learn the ways many more captivating moments from the 1970s.
Newest Leaky discovery: footprints 3.6 million years old, What about nuclear energy, Warm springs Indians Carve, Killer Whale attack
The complete National Geographic on CD-ROM was produced from archive of magazines collected in a central repository and is not representative of any single regional edition of National Geographic magazine.
Minimum requirements for Windows: Pentium 90MHz or faster, 24MB RAM, 70MB free hard-disk space, SVGA video card supporting 16-bit color, 16-bit sound card and speakers, 4x CD-ROM drive.
Minimum requirements for Macintosh: PowerPC or higher, System 7.5 or higher, 32MB RAM, 70MB free hard-disk space, 640x840 16-bit color monitor, 4x CD-ROM drive.
Keywords: Gorilla; Ethiopia; Thor Heyerdahl